Influence of principals’ performance in training teachers in Information Communication Technology on usage of ICT for teaching and learning in secondary schools - Otieno, Kagutu Joseph; Ajowi, Jack O.; Gudo, Calleb O. (International Journal of Education and Researc h, 2018)
The focus of this study was to investigate how principals’ performance of leadership roles influenced usage of ICT for teaching and learning in secondary schools. The objective of the study was to analyze the influence that performance of principals in training teachers in ICT has on usage of ICT for teaching and learning in schools. Concurrent triangulation within mixed methods research design was used. Stratified random sampling was used to draw 99 principals from 132 distributed in seven sub-counties. Saturated sampling technique was used to sample 28 principals, 28 deputy principals and 35 Heads of Department (HODs) for interviews. Data were gathered using questionnaires for principals and interview schedules for principals, deputy principals and HODs. Questionnaire reliability was ascertained at (r) = 0.739using the split-half technique. Results revealed that performance of principals in training teachers in ICT (α=.338, p>.05) statistically significantly influenced usage of ICT for teaching and learning. It was concluded that performance of principals in training teachers in ICT had an impact on usage of ICT for teaching and learning in schools in Kisumu County. It was recommended that principals should complement the Government’s efforts by training teachers in ICT usage.
Keywords: Influencing; Information Communication Technology; Performance; Teaching learning; Training